PENGARUH MINAT MENJADI BIDAN, DUKUNGAN KELUARGA, DAN KEDISIPLINAN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA STIKES AISYIYAH SURAKARTA - Nindya Kurniawati (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2015)
Achieving ability Kepmenkes No.900/2002 midwife in accordance with the demands contained in the ability of midwives as professionals and independent . The achievement of these capabilities can be started from the educational institution based on the core competencies of midwives . The ability to measure the achievement of measurable learning achievement premises . The high interest in becoming a midwife , the amount of family support , the discipline is followed in the study would affect learning achievement . The purpose of this study was to determine the effect of interest into midwife , family support , and discipline of learning on student achievement. This study is an observational analytic cross sectional approach . The study was conducted in December 2013 until May 2014 . The sample amounted to 88 respondents. The sampling technique using simple random sampling. Measuring instrument using a questionnaire with likert scale . Analysis of data using multiple linear regression analysis with α of 5% . The results of multiple linear regression analysis of the independent variable of interests being midwife ( X1 ) , family support ( X2 ) , and the discipline of learning ( X3 ) on the dependent variable learning achievement ( Y ) p-value obtained ( 0.000 ) <α ( 0.05 ). Value of F ( 126.687 )> F (2.72 ) . Effective contribution ( R2 ) jointly acquired 0.819. There is a strong positive influence and significant correlation between interest in becoming a midwife , family support , and discipline of learning on student achievement STIKES Aisyiyah Surakarta .